Productive model of evergreen oak and annual pastures in Extremadura (Spain) - Etienne A.; Valderrama J.M.; Díaz-Ambrona C.H. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Dehesa or montado is a Mediterranean agro-silvo-pastoral system characterized by the presence of trees, Quercus ilex and Q. suber, and annual pastures. Acorn production is used to feed pigs, and pasture is grazed by cows, sheep or goats. The surface area of Extremadura dehesas accounts for one million hectares, 95% of which is Q. ilex. The objective was to identify the optimal stocking rate. A simulation model was used to determine stoking rates for Iberian pigs and dry cows in Extremadura. The model runs with daily weather data from Extremadura Station Network, soil from Extremadura soil database, and tree cover from the Third National Forest Survey. A database was built for each input and was displayed using ArcGis. Simulated average pasture yield was 3615 kg/ha and acorn production was 249 kg/ha. The model estimated that the optimal stocking rate ranges from 0.3 to 0.8 Iberian pigs per ha and from 0.1 to 0.9 cows per ha.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)